Vapour-liquid-solid growth of ZnO-ZnMgO core-shell nanowires by gold-catalysed molecular beam epitaxy - Kennedy,OW; White,R; Shaffer,MSP; Warburton,PA (Nanotechnology, 2019)
Nanowire heterostructures, combining multiple phases within a single nanowire, modify functional properties and offer a platform for novel device development. Here, ZnO/ZnMgO core–shell nanowires are grown by molecular beam epitaxy. At growth temperatures above 750 °C, Mg diffuses into ZnO making heterostructure growth impossible; at lower shell-growth temperatures (500 °C), the core–shell structure is retained. Even very thin ZnMgO shells show increased intensity photoluminescence (PL) across the ZnO band-gap and a suppression in defect-related PL intensity, relative to plain ZnO nanowires. EDX measurements on shell thickness show a correlation between shell thickness and core diameter which is explained by a simple growth model.